Impact of Physics Learning to Improving Learners' Generic Science Skills: A Review - Aris Doyan; Susilawati Susilawati; Syamsul Hakim; Mahdini Mahdini; Hamidi Hamidi (Jurnal Penelitian Pendidikan IPA, 2022)
This study is a Literature Review article that aims to identify the most effective learning model to improve the generic science skills of learners in physics learning. A search of literature study articles obtained as many as fifteen articles that met the inclusion criteria and were relevant for review. The results of the research show that many learning models can be applied in physics learning to improve the generic science skills of learners. The findings show that the most effective guided inquiry learning model for improving students' generic science skills was characterized by the achievement of learners' scores of 91.00.